Can Universities Help “Build Back Better” in Education? The Socially Embedded University Responds to the Covid-19 Pandemic - Reimers, Fernando M. (Frontiers in Sustainability, 2021)
The high impact disruptions in the external environment caused by the Covid-19 pandemic revealed the socially embedded character of the university. University collaborations with schools during the Pandemic suggest that they are institutions open to their external environment, capable of learning from and with their environment. Drawing on a survey administered to 101 universities around the world, I examine how Universities built partnerships with schools to sustain educational opportunity during the pandemic. The results are informative of the evolving nature of higher education and its mission. They illustrate the responsiveness of universities to societal needs. The findings help us understand how socially connected the university is to its surrounding context, and how it interprets its responsibility to be an engine of social innovation at a time of great unexpected need.